La antimemoria autobiográfica en historias del Country Cluby el Barrio Marconi de Alfredo Bryce Echenique - Rodríguez, Héctor Alexander Valeriano (2023)
The research paper "Autobiographical Antimemory in Stories from the Country Club and Marconi Neighborhood by Alfredo Bryce Echenique" aims to compare three stories by the Peruvian author: the short story "Una mano en las cuerdas (Páginas de un diario) (1968), the adapted chapter titled "Country Club" from the novel A World for Julius (1970), and the adaptation of the chapter "Lucho Gatica and Nat King Cole" from the novel No me esperen en abril (1995), titled "El mes más feliz de todo el año", all included in the compilation called Historias del Country Club y del barrio Marconi (2016). The objective is to analyze similarities in plots, characters, and sociocultural context, relying on André Malraux's Antimemory and Philippe Lejeune's Autobiographical Pact. Another purpose is to promote the relevance of Alfredo Bryce Echenique's work in Latin American literature, particularly in Brazil, where he is less known. Bryce Echenique is a prominent figure of the Post-Boom movement in 20th-century Latin American literature, characterized by incorporating biographical experiences, autofiction, and antimemory into his narratives. His stories transport readers to the urban atmosphere of Lima in the second half of the 20th century, addressing themes such as loneliness, the self-exile of Peruvians abroad, and social discrimination. The methodology involves thorough research of interviews, essays, and theses related to Bryce Echenique, along with an analysis of the concepts of Malraux's Antimemory and Lejeune's Autobiographical Pact. This provides a deep understanding of how memory and autobiography influence his literary production. In summary, this dissertation aims to shed light on Bryce Echenique's works through a comparative analysis based on autobiographical and antimemory theories. It is expected to contribute to a better understanding and appreciation of this outstanding Peruvian author in the Brazilian academic context and in 20th-century Latin American literature.